Effect of Different Pot Sizes and Growth Media on the Agronomic Performance of Jatropha curcas - Geply, O.A.; Baiyewu, R.A.; Adegoke, I.A.; Ayodele, O.O.; Ademola, I.T. (Pakistan Journal of Nutrition, 2011)
This research study was carried out to investigate the effect of different pot sizes and growth media on the growth of Jatropha curcas. Two different pot sizes (5 cm by 10 cm) for big pot sizes and (2½ cm by 2½ cm by 6 cm) for small pot sizes and 3 different growth media made up of Top Soil, River Sand and Sawdust were used. Relative comparison in Jatropha curcas plant agronomic parameter such as plant height, stem girth and number of leaves, was determined and the values were analyzed using Statistical Package for Social Science (SPSS). The result of the analysis shows a significant difference in the combination factor of treatment and weeks, for plant height, stem girth and number of leaves. From the mean value, River Sand in big pot (RB) has the highest value in height and girth with 7.2217 cm, 0.9950 mm respectively. While the highest number of leave was counted from Top Soil in big pot (TB) with 6.7333 cm. Based on the agronomic result obtained in this study, it can therefore be concluded that the best soil media for growing Jatropha curcas is River Sand and the best pot size is big pot (5 cm by 10 cm).